The Procedures of Translating Abbreviations in English Medical Texts into Indonesian - Dian Susanthi, I Gusti Ayu Agung; Artawa, Ketut; Putra Yadnya, Ida Bagus; Sri Satyawati, Made (e-Journal of Linguistics, 2019)
This study reveals the procedures of translating abbreviations in English medical texts into Indonesian. It aims at (1) identifying how the abbreviations of English medical terms are translated into Indonesian and (2) identifying the phrase of the SL transferred into Indonesian. This study discusses three procedures of translating abbreviations of English medical terms which are reformulated based on the need of this study, i.e.(1) translating the abbreviation into abbreviation (borrowing); this procedure showed that the abbreviations of English medical terms were translated into abbreviations, in which borrowing was found (2) translating the abbreviation into abbreviation (adaptation); this procedure showed that the abbreviations of English medical terms were translated into abbreviations, in which  adaptation was found  (3) translating the abbreviation into phrase; this procedure showed that the abbreviation was translated into phrase. The data were taken from the translation of a medical textbook, Oxford Handbook of Midwifery (2006) and its translation into Indonesian Buku Kebidanan Oxford (2010). The results showed that there were three types of procedures used to translate the abbreviations in this study referred to as translating abbreviation to abbreviation (borrowing), and translating the abbreviation into abbreviation (adaptation), and translating the abbreviation into phrase.